1997
DOI: 10.1128/iai.65.4.1228-1236.1997
|View full text |Cite
|
Sign up to set email alerts
|

Complement-mediated serum sensitivity among spirochetes that cause Lyme disease

Abstract: Borrelia burgdorferi-related isolates were tested for their sensitivity to normal human serum (NHS) and their ability to activate complement. By dark-field microscopy, electron microscopy, and subsurface plating, it was shown that exposure of a Borrelia garinii isolate to 10% or more NHS resulted in immobilization, blebbing, and killing of the spirochetes. These effects were mediated by complement, since they were not seen after heat treatment of NHS, in the presence of EDTA, or in an agammaglobulinemic serum.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(75 citation statements)
references
References 58 publications
3
64
0
Order By: Relevance
“…We found that blood treatment is essential to demonstrate the CspZ-mediated FH-binding activity to confer spirochete survival in sera (Figure 4). It is noteworthy that we count immotile cells as the indicator of cell death by dark-field microscopy, a method that has been commonly used to identify killed cells (Alitalo et al, 2001;Alitalo et al, 2005;Brooks et al, 2005;Kraiczy, Hunfeld, Peters, et al, 2000;McDowell et al, 2011;van Dam et al, 1997). Furthermore, the lack of motility is the most apparent sign of complement-mediated bacterial killing, which allows determination of cell viability microscopically without the need for the extended duration of time to cultivate spirochetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that blood treatment is essential to demonstrate the CspZ-mediated FH-binding activity to confer spirochete survival in sera (Figure 4). It is noteworthy that we count immotile cells as the indicator of cell death by dark-field microscopy, a method that has been commonly used to identify killed cells (Alitalo et al, 2001;Alitalo et al, 2005;Brooks et al, 2005;Kraiczy, Hunfeld, Peters, et al, 2000;McDowell et al, 2011;van Dam et al, 1997). Furthermore, the lack of motility is the most apparent sign of complement-mediated bacterial killing, which allows determination of cell viability microscopically without the need for the extended duration of time to cultivate spirochetes.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 5 × 10 6 cells of mid-log B. burgdorferi were cultivated in BSK-II complete medium with 5% human blood with the buffy coat removed. This concentration of human blood does not reduce the growth and motility of serum-sensitive strains (Breitner-Ruddock, Wurzner, Schulze, & Brade, 1997;Hart, Nguyen, et al, 2018;Kenedy & Akins, 2011;van Dam et al, 1997). The human blood was supplemented with a cocktail of antibiotics (final concentration: 50 μg ml −1 of rifampicin, 20 μg ml −1 of phosphomycin, and 2.5 μg ml −1 of amphotericin) to prevent potential bacterial and fungal contamination.…”
Section: Figurementioning
confidence: 99%
“…Considering the close relation of dog and cat with human, it is important to know whether co-feeding can take place in these carnivores. In human, studies are available [17,26] and B. afzelii, and its influence on the pathogenic and clinical manifestations. Our study is an extension of previous reports by assessing the complement sensitivities of more genospecies.…”
Section: Discussionmentioning
confidence: 99%
“…To inhibit the classical pathway of complement activation, some aliquots from each animal species were incubated with 10 mM EGTA, 4 mM MgCl 2 in veronal buffer saline (VBS) at 37°C for 30 min. Some serum aliquots from each animal species were incubated with 10 mM EDTA in VBS at 37°C for 30 min to inactivate both pathways (classical and alternative) [17].…”
Section: Collection Of Sera and Borrelia Strainsmentioning
confidence: 99%
See 1 more Smart Citation